The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1371/journal.pone.0241136
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age on the gap-prepulse inhibition of the cortical N1-P2 complex in humans as a step towards an objective measure of tinnitus

Abstract: The gap-prepulse inhibition of the acoustic startle reflex has been widely used as a behavioral method for tinnitus screening in animal studies. The cortical-evoked potential gap-induced inhibition has also been investigated in animals as well as in human subjects. The present study aimed to investigate the effect of age on the cortical N1-P2 complex in the gap-prepulse inhibition paradigm. Fifty-seven subjects, aged 20 to 68 years, without continuous tinnitus, were tested with two effective gap conditions (em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 68 publications
0
2
0
2
Order By: Relevance
“…There was no correspondence between the background frequency and the tinnitus-pitch, which was presumably affected by stimulus properties and higher cognitive processing. Another study [ 145 ] found that the neural GPI ratio (gap/no gap) using the N1–P2 amplitude was affected by the gap duration and background frequency, and there is a lower effect of age on the specific gap duration. Therefore, an appropriate combination of gap duration and background frequency will enhance the sensitivity and specificity and decrease the influence of confounding factors, such as age, when tinnitus is assessed with the GPI paradigm.…”
Section: Electrophysiological Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no correspondence between the background frequency and the tinnitus-pitch, which was presumably affected by stimulus properties and higher cognitive processing. Another study [ 145 ] found that the neural GPI ratio (gap/no gap) using the N1–P2 amplitude was affected by the gap duration and background frequency, and there is a lower effect of age on the specific gap duration. Therefore, an appropriate combination of gap duration and background frequency will enhance the sensitivity and specificity and decrease the influence of confounding factors, such as age, when tinnitus is assessed with the GPI paradigm.…”
Section: Electrophysiological Methodsmentioning
confidence: 99%
“…Factors, such as sex, age, and hearing conditions have an impact on the gap process [ 145 , 149 , 150 , 151 ]. In future research, attention should still be paid to matching these, and intra-group differences should be controlled as much as possible to reduce the degree of dispersion.…”
Section: Electrophysiological Methodsmentioning
confidence: 99%
“…Sabe-se que em humanos, a diminuição ou a ausência do PPI sugere transtornos neuropsiquiátricos como a esquizofrenia (Swerdlow, 2009) e o transtorno de déficit de atenção e hiperatividade (Lemvigh et al, 2020). O teste de GPIAS é utilizado tanto em animais quanto em humanos, principalmente para detecção do tinnitus e disfunções no desenvolvimento do processamento temporal auditivo (Anderson & Linden, 2016;Fitch et al, 2008;Ku et al, 2020;Lu et al, 2008) e alterações na detecção da ausência de som já foram descritas em indivíduos com o transtorno do espectro autista (Bhatara et al, 2013) e em condições neurodegenerativas e neurodesenvolvimentais como na velhice, na doença de Alzheimer e em disfunções de linguagem e leitura (Gordon-Salant & Fitzgibbons, 1993;Iliadou et al, 2017;McArthur & Bishop, 2001;Snell, 1997;Strouse et al, 1998).…”
Section: O Circuito Do Reflexo Acústico Do Sobressaltounclassified
“…Regiões como o hipocampo central, colículo inferior, córtex pré-frontal e a própria conectividade córtico-cortical podem modular o gatilho sensório motor acústico e o núcleo coclear ventral (Dissanayake et al, 2008;Khani et al, 2019;Tripathi et al, 2021;Vohs et al, 2009;Witten et al, 2014) Alguns trabalhos mostram o envolvimento do DCN no gatilho sensório motor acústico, mas aferido pelo GPIAS (Han et al, 2019;Heeringa et al, 2018). O teste de inibição do sobressalto a partir de um pré-pulso de silêncio (GPIAS) é utilizado para aferir o ASG e avaliar a presença do tinnitus em animais e em humanos (Anderson & Linden, 2016;Ku et al, 2017Ku et al, , 2020Shen, 2014). O tinnitus é um sintoma onde ocorre a percepção de um som fantasma em uma frequência característica e estudos relacionam o DCN como a origem do tinnitus devido a uma hiperexcitabilidade dos neurônios fusiformes com uma redistribuição das projeções glutamatérgicas aos núcleos cocleares (Heeringa et al, 2018;S.…”
Section: A Privação Acústica De Longo Prazo Altera O Funcionamento Do...unclassified